Türkiye’de radyo yayın tekeli döneminde siyasal,toplumsal yapı-radyo programcılığı,yayıncılığı etkileşimi - Kayador, Vakur (My University, 1999)
POLITICIAL, SOCIAL STRUCTURE AND RADIO PROGRAMMING, RADIO BROADCASTING INTERACTION DURING MONOPOLISTIC RADIO BROADCASTING ERA IN TURKEY In this thesis, Turkish radio broadcasting of 1927-1993 period has been studied, This is the period of monpolistic radio broadcastıng in Turkey. The effects of political, social structure on radıo programming during the era have been evaluated. Years between 1926-1936 are the early years of the foundation of Turkish Republic. When everything was being rebuilt in Turkey, radio broadcasting was started by a private joint stock company-Turkish Wireless, Telegram (T.T.T.A.Ş.) However, because the founders of this company were actually public service officers, the company stayed within the total control of the state. In 1936, the company was transferred to PTT, a public service company in charge of postal, telegram and telephone services.Howewer, following forteen years did not rise radio broadcasting services to a professional level. In 1940, Turkish radio broadcasting was transferred to the General Directorate of Printing and Publishing. During the Second World War, Turkish radio stations realized a very successful news programming. Between 1946 and 1960 the governments realized the enormous effect of radio broadcasting on public. When Democrat Party was in pover, radio broadcasting was taken under strict control of the government. This control had continuously been exercised at various levels and wasy on radio programming until 1993, the year when broadcast monopoly was broken and pluralistic broadcasting started. This control and interaction is analysed within the context of the periods involved and progress in broadcasting. Indepth interviews with programmers are conducted to disclose the background. The period between 1963, when the radio stations are subjected to Turkish Radio Television monopoly, and 1971 military intervention constitutes a chapter. Events from 1971 to the 1982 Constitution by which radio ard television broadcasting was restructured, is the subject of another chapter. The last chapter covers the period between 1982 and 1994, when the private television channels gained legal identity. This study reveals that the goverments have intensly controlled the radio programming and broadcasting parallel to the efficiency of the radio brocasting. TÜRKİYE'DE RADYO YAYIN TEKELİ DÖNEMİNDE SİYASAL, TOPLUMSAL YAPI-RADYO PROGRAMCILIĞI, RADYO YAYINCILIĞI ETKİLEŞİMİ Tez çalışmasında 1927-1993 dönemi Türkiye radyoculuğu ele alınmıştır. Bu dönem Türkiye'de radyo yayın tekelinin olduğu bir dönemdir. Bu dönemde siyasal toplumsal yapının radyo yayıncılığı ve radyo programcılığına nasıl yansıdığı değerlendirilmiştir. 1926-1936 yılları, Cumhuriyetin kuruluş dönemleridir. Her şeyiyle yeniden inşa edilen Türkiye'de radyoculuk. Bir özel kuruluş olan Türk Telsiz Telgraf Anonim Şirketi (T.T.T.A.Ş) eliyle başlatılmıştır. Ancak kurucuları bürokrat olan bu şirket bütünüyle devlet denetiminde kalmıştır. 1936 yılında bir kamu kuruluşu olan PTT'ye devredilmiştir. Bu on dört yıl, profesyo-nel anlamda radyoculuğun başlamasını sağlayamamıştır. 1940 yılında Türkiye radyoculuğu Basın Yayın Genel Müdürlüğü'ne devredilmiştir. 1963 yılına kadar süren bu dönemin başlangıcı II.Dünya Savaşı yıllarını kapsamaktadır. Bu sıra- larda Türkiye radyoculuğu çok başarılı haber yayıncılığı yapmıştır. 1946'dan 1960 yılına kadar geçen süre içinde radyonun olağanüstü etkisi siyasal yönetimler tarafından anlaşılmıştır. Demokrat Parti iktidarı döneminde radyolar çok yoğun biçimde baskı altında tutulmuşlardır. 1994 yılında yayın tekelinin kırılıp, çoğulcu yayın etkinliğinin başladığı döneme kadar bu baskı farklı dönemlerde değişik biçimlerde radyo programlarını etkilemiştir. Bu etkileşim, dönemlerin genel özellikleri ve radyoculukta yaşanan gelişmelerle bütünlük içinde incelenmiştir.Programcılarla derinlemesine mülakatlar yapılarak durum ortaya konmaya çalışılmıştır. Radyoların TRT (Türkiye Radyo Televizyon Kurumu) bünyesinde bir araya geldikleri 1946'ten 1971 askeri müdahalesine kadar geçen süre bir bölüm olarak değerlendirilmiştir. 1971'den 1982 Anayasası ile radyo televizyon düzeninin yeniden oluşturulduğu dönem bir başka bölümdür. Son bölüm ise 1982'den 1993'teki özel televizyonların yasal kimlik kazandıkları döneme kadar geçen süredir. Bu çalışmada; radyonun etkinliğine göre, her dönemde siyasal yapının radyo yayıncılığı ve programcılığı üzerinde yoğun baskısının olduğu saptanmıştır.
Keywords: İletişim (Telekomünikasyon); RADYO; Radyo yayıncılığı; RADYO YAYINCILIĞI; Telsiz iletişimi